Relevance of Ibn Fudi's Views on the Etiquette of Dining and Hospitality in His Diyā’u-t-Ta’wīl to Contemporary Yoruba Society - Hassan, Abdullah Sayuti; Saheed Adewale BADMUS (Al-Mahkamah: Islamic Law Journal, 2024)
Social etiquette—including dining and hospitality etiquette—has almost disappeared in contemporary Yoruba society. This is because some Yoruba individuals have begun to imitate Western practices in everything. Behaviours that do not align with Islamic etiquette in dining and hospitality have become common, particularly among the youth, including young Muslims in Yoruba lands. In this society, those who attempt to adhere to these etiquettes are often considered as nonconformists and sometimes labelled as extremists. This paper, therefore, aims to study the application of dining and hospitality etiquette in the Yoruba community through the views of Ibn Fudi in his commentary entitled: “Diyā’u-t-Ta’wīl”. To achieve the aim of this study, the research employs an analytical method to clarify the etiquettes of dining and hospitality as explained by Ibn Fudi in his Tafsir. in relation to the contemporary Yoruba society. The findings of this study show that deviations from proper dining and hospitality etiquette are widespread in Yoruba land such as eating or drinking with the left hand or while walking, expecting the host to taste the food first before the guest eats and the refusal to dine with those of lower status, among other practices. These behaviours result has caused negative impacts on individuals and society, such as diminished affection, social fragmentation and wishing ill upon others. The solution lies in applying the dining and hospitality etiquettes as outlined in Ibn Fudi’s commentary. The study suggests that scholars in Yorubaland should link the social etiquettes found in Ibn Fudi’s Tafsīr to contemporary Yoruba society for societal improvement. They should also highlight the drawbacks of neglecting Islamic etiquettes, especially in dining and hospitality, and the benefits that their application brings to individuals and the community. Members of the community should also be committed to whatever will help them uphold these etiquettes.